Effect of gum Arabic as natural prebiotic on intestinal ecosystem of post-hatched broiler chicks - Hani Hasan Al-Baadani; Rashed Abdullah Alhotan; Mahmoud Mustafa Azzam; Ibrahim Abdullah Alhidary; Abdulrahman Salem Alharthi; Abdulaziz Abdullah Al-Abdullatif (Journal of Animal Science and Technology)
The purpose of the current study was to investigate the effects of gum Arabic supplementation on short-chain fatty acids, cecal microbiota, immune-related gene expression, and small intestinal morphology in post-hatched broiler chicks. On the day of hatching, four hundred thirty-two commercial male broiler chicks were randomly allocated into six treatments with twelve cages as replicates of six chicks each for 24 days. Dietary treatments (T1 to T6) were supplemented with 0.0, 0.12, 0.25, 0.50, 0.75, and 1.0% gum Arabic to the basal diet, respectively. Performance parameters, short-chain fatty acid concentration, quantification of microbiota and immune response gene expression (pre-inflammatory cytokines, mucin-2, and secretory immunoglobulin A), and histomorphometry of the small intestine were measured. According to our results, daily weight gains in T2 and the production efficiency index increased in T2 to T4, whereas daily feed intake decreased in T2, T3, T5, and T6, but feed conversion ratio improved. Concentration of lactate, acetate, butyrate, and total short-chain fatty acid increased in T2, T3, T5, and T6. Propionate ‎in T2 T3, T4, and T6 and format in T2, T5, and T6 also increased. Lactobacillus spp. quantitatively increased from T3 to T6, whereas Bacteroides spp. decreased in T3 and T5. Other microbiota quantitatively showed no effect of dietary supplements. IL-1β, TNF-α, and MUC-2 decreased in T2 to T6 and IL-12 in T3, whereas INF-Y increased in T4 to T6 and SIgA in T4. All histometeric parameters of the duodenum, jejunum, and ileum improved with dietary supplementation. We conclude that the administration of gum Arabic resulted in an improvement in overall performance, fermentation metabolites, and modification of microbiota and immune response with improved histomorphometry in the intestines of young chicks.